2021
DOI: 10.1186/s12887-021-02949-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between early fluid overload and mortality in critically-ill mechanically ventilated children: a single-center retrospective cohort study

Abstract: Background Positive fluid overload (FO) may cause adverse effect. This study retrospectively analyzed the relationship between early FO and in-hospital mortality in children with mechanical ventilation (MV) in pediatric intensive care unit (PICU). Methods This study retrospectively enrolled 309 children (ages 28 days to 16 years) receiving invasive MV admitted to the PICU of Xinhua Hospital from March 2014 to March 2019. Children receiving MV for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…High DP, more than 15 cm H 2 O, in acute hypoxemic respiratory failure children was independently associated with There is currently no study of DP in PMV. The median maximum DP in our study was 16 cm H 2 O (IQR: 13-20) and DP tended to be greater when comparing PMV > 30 days with PMV > 14-30 days [17 (14-20) vs. 15 (13)(14)(15)(16)(17)(18), P = 0.09] which supports previous studies (17, 21). Although deaths had a significantly higher median maximum DP than survivors [19 (16)(17)(18)(19)(20)(21)(22) vs. 15 (12)(13)(14)(15)(16)(17)(18) cm H 2 O, P < 0.001], it was not an independent predictor of mortality after multivariate analysis (even with a cutoff of 17 cm H 2 O).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…High DP, more than 15 cm H 2 O, in acute hypoxemic respiratory failure children was independently associated with There is currently no study of DP in PMV. The median maximum DP in our study was 16 cm H 2 O (IQR: 13-20) and DP tended to be greater when comparing PMV > 30 days with PMV > 14-30 days [17 (14-20) vs. 15 (13)(14)(15)(16)(17)(18), P = 0.09] which supports previous studies (17, 21). Although deaths had a significantly higher median maximum DP than survivors [19 (16)(17)(18)(19)(20)(21)(22) vs. 15 (12)(13)(14)(15)(16)(17)(18) cm H 2 O, P < 0.001], it was not an independent predictor of mortality after multivariate analysis (even with a cutoff of 17 cm H 2 O).…”
Section: Discussionsupporting
confidence: 91%
“…The median maximum DP in our study was 16 cm H 2 O (IQR: 13-20) and DP tended to be greater when comparing PMV > 30 days with PMV > 14-30 days [17 (14-20) vs. 15 (13)(14)(15)(16)(17)(18), P = 0.09] which supports previous studies (17, 21). Although deaths had a significantly higher median maximum DP than survivors [19 (16)(17)(18)(19)(20)(21)(22) vs. 15 (12)(13)(14)(15)(16)(17)(18) cm H 2 O, P < 0.001], it was not an independent predictor of mortality after multivariate analysis (even with a cutoff of 17 cm H 2 O). Several studies reported an association between fluid accumulation and MV duration, PICU LOS and mortality rate (18)(19)(20).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations